Trends in breast cancer mortality and diet in England and Wales from 1911 to 1980. - Key, T; Darby, S; Pike, M (1987)
A paper in a previous volume of this journal (Ingram, DM, Nutr Cancer 3, 75-80, 1981) reported that at the beginning of World War II there was a marked decrease in breast cancer mortality in England and Wales that coincided with a marked reduction in the consumption of sugar, meat, and fat, and a marked increase in the consumption of cereals and vegetables. Reexamination of the mortality data described in that paper shows that the apparent sudden decrease in breast cancer mortality at the beginning of World War II is an artefact caused by a change in the method of selecting the cause of death from jointly stated causes, which was introduced in 1940. After adjusting for this change, trends in age-specific mortality rates are described. Breast cancer mortality rates were greater in 1980 than in 1911 in the age group of 35-84 years, but this overall increase was interrupted by a period of decreasing mortality between the 1930s and the 1950s in the age group of 50-69 years. It is possible that some of this decrease was due to dietary changes; however, the evidence is poor and other factors that affect incidence and survival must be considered.